In-App Purchase in Japanese Free-To-Play Mobile Game: The Motivation of Indonesian Players - Khaled, Prima Diana; Iskandar, Kurniawaty (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Japan is one of the countries with the largest mobile game industry in the world. One type of Japanese game that can be downloaded for free via application stores on smartphone devices is known as the mobile game Free-to-play. In mobile game free-to-play, there is additional services such as in-app purchases or microtransaction activities. In-app purchases on the free-to-play mobile game offer several virtual objects that can be used in the game. This study uses the otaku animal database and IGD (Internet Game Disorder) theoretical framework to understand Japanese free-to-play mobile gameplayer’s motivation to make in-app purchases in Indonesia by using structured interview methods and interpretive explanation data analysis techniques. From the results of interviews with five speakers who are Japanese free-to-play mobile game players in Indonesia, it is known that the motivation of these players in making in-app purchases is to get the characters they want. Furthermore, the motivation to get a specific character is determined by the character design and the story background of the Japanese free-to-play mobile game. In addition to the character attraction factor, the existence of character abilities that can support the game to form a strong team is also why players take fast ways to get certain characters through in-app purchase services.